2018
DOI: 10.1111/ans.14814
|View full text |Cite
|
Sign up to set email alerts
|

Inpatient rehabilitation did not positively affect 6‐month patient‐reported outcomes after hip or knee arthroplasty

Abstract: Our study has shown that inpatient rehabilitation after hip or knee arthroplasty did not positively affect 6-month patient-reported satisfaction, expectation, pain, quality of life, activities of daily living scores, when compared with subjects who were discharged direct to home. A significant average saving of $5600 per patient with the use of home discharge is a promising avenue for health cost reduction, and health resource distribution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…In other words, the more intensely supervised facility-based programs i.e., inpatient or clinic-based programs, do not provide superior recovery to that seen in domiciliary or other forms of home program after unilateral TKA [3040] or THA [39, 4145] for uncomplicated patients. The randomized trial evidence is corroborated by several prospective and retrospective observational studies [12, 13, 23, 4649]. We also know that the more intensely supervised facility-based programs including inpatient rehabilitation are delivered at far greater cost than programs not including inpatient rehabilitation [12, 13, 45] and may not be cost-effective [39, 50].…”
Section: Introductionmentioning
confidence: 93%
“…In other words, the more intensely supervised facility-based programs i.e., inpatient or clinic-based programs, do not provide superior recovery to that seen in domiciliary or other forms of home program after unilateral TKA [3040] or THA [39, 4145] for uncomplicated patients. The randomized trial evidence is corroborated by several prospective and retrospective observational studies [12, 13, 23, 4649]. We also know that the more intensely supervised facility-based programs including inpatient rehabilitation are delivered at far greater cost than programs not including inpatient rehabilitation [12, 13, 45] and may not be cost-effective [39, 50].…”
Section: Introductionmentioning
confidence: 93%
“…and "What is your satisfaction with the surgical results?" (27). In the present survey we developed in this study, there are items related with physiotherapy service.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers used the Visual Analog Scale, which was rated between 0 and 10 without questionnaire in satisfaction evaluation (26). In another study, two questions were used to evaluate inpatient satisfaction after the surgery: “Would you repeat the same surgery under the same conditions?” and “What is your satisfaction with the surgical results?” (27). In the present survey we developed in this study, there are items related with physiotherapy service.…”
Section: Discussionmentioning
confidence: 99%
“…However, emerging remote clinical studies involving wearable technologies at Kaiser (15) suggest that the potential for fewer clinical visits and thus fewer copayments along with reduced time invested in appointments and travel to clinics would be strong motivators for initial adoption by patients. Home-based exercises (i.e., supervised or unsupervised) are preferred by patients who were recently discharged home after through-knee amputations due to convenience (28)(29)(30). Systematic reviews and meta-analyses have further confirmed that supervised rehabilitation exercises do not provide additional benefits when compared to home-based rehabilitation exercises (31)(32)(33).…”
Section: Cost Considerationsmentioning
confidence: 99%